Mortality among white, black, and Hispanic male and female state prisoners, 2001–2009. (December 2016) - Wildeman, Christopher; Carson, E. Ann; Golinelli, Daniela; Noonan, Margaret E.; Emanuel, Natalia
Abstract: Although much research considers the relationship between imprisonment and mortality, little existing research has tested whether the short-term mortality advantage enjoyed by prisoners extends to Hispanics. We compared the mortality rates of non-Hispanic white, non-Hispanic black, and Hispanic male and female state prisoners to mortality rates in the general population using data from the Deaths in Custody Reporting Program, the National Prisoner Statistics, the National Corrections Reporting Program, and the Centers for Disease Control and Prevention. The results indicate that the mortality advantage for prisoners was greatest for black males, followed by black females, Hispanic males, white females, and white males. Hispanic female prisoners were the only group not at a mortality advantage relative to the general population, with an SMR of 1.18 [95% CI: 0.93–1.43]. Taken together, the results suggest that future research should seek to better understand the curious imprisonment–mortality relationship among Hispanic females, although given the small number of inmate deaths that happen to this group (~0.6%), this research should not detract from broader research on imprisonment and mortality.